Pelatihan Pembangkit Listrik Tenaga Surya Jenis Off-Grid di BLK Don Bosco Tambolaka-Sumba Barat Daya: Off-Grid Solar Power Plant Training at BLK Don Bosco Tambolaka-Southwest Sumba - Pratomo, Leonardus Heru; Setiawan, Florentinus Budi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The requirement for instructors who have the theoretical and practical skills of a training center is an absolute necessity. Don Bosco Vocational Training Center in Tambolaka, Southwest Sumba is a place to conduct many trainings, one of which is a solar power plant. Don Bosco Vocational Training Center has adequate equipment but the instructors have not been skilled in both theory and practice. Solar power plant training in theory and practice is a desired solution to obtain experience directly. The service aims to train instructors of the Don Bosco Vocational Training Center and the local community who want to know understand and practice directly. This activity is carried out through several stages: theoretical studies, solar panels in series and parallel and irradiance measurements, batteries and how to determine their health, solar charge control, single-phase inverters, hybrid single-phase inverters, protection systems and types of cables and connectors used. Practices are conducted on-site after the theory is comprehended, and off-grid practices are performed with two types: a combined solar charge control inverter and a hybrid inverter and troubleshooting. From this activity the interest of the instructors is very enthusiastic, this can be seen from the first day the instructors have been able to assemble all the equipment properly and function, on the second day it is repeated to ensure the performance of the instructors is correct along with troubleshooting. This success has proven that the Don Bosco Vocational Training is the center of solar power plant training in Southwest Sumba.